Case report: A rare case of multifocal, combined lymphatic-venous malformation - Pham, Hien Duy; Tran, Duy Le Dinh; Dang, Thom Hoang; Nguyen, Luan Vo Mac; Dang, Trang Thu; Nguyen, Linh Vu Thuy; Nguyen, Quang Thanh (Frontiers in Medicine, 2024)
Vascular malformations, including lymphatic-venous malformations (LVMs), are complex and can lead to significant morbidity. This case report details the management of a rare multifocal, combined LVM in a 3-month-old male, misdiagnosed as a right inguinal hernia prenatally. Postnatal imaging revealed multiloculated cystic masses extending from the mons pubis to the right groin, scrotum, and thigh. Doppler ultrasound and MRI demonstrated the extent of the masses, with the largest cyst measuring 4 x 4 x 2 cm. Initial surgical excision and debulking were performed; however, the lesion recurred six months later. Given the complexity and involvement of truncal vessels, complete excision was not feasible, and sclerotherapy with intralesional Bleomycin injections was initiated. After the first Bleomycin injection, a significant reduction in lesion size was observed. However, six months later, the lesion recurred and enlarged, necessitating a second Bleomycin injection. Subsequent follow-ups showed further reduction in lesion size. Unfortunately, two years later, the patient experienced diffuse cystic infiltration of the pelvis and right lower extremity due to treatment delays caused by the COVID-19 pandemic. Imaging at this stage revealed a cystic mass in the right pelvic cavity measuring 10 x 6 x 5 cm. Two additional sessions of Bleomycin injections were performed, resulting in a successful resolution of the cystic masses. Regular follow-ups have shown that the LVMs remain under control, with no symptoms and no concerns from the family. This case underscores the complexities involved in diagnosing and managing multifocal, combined LVMs. It suggests that Bleomycin sclerotherapy can be a valuable, minimally invasive alternative to more extensive surgical procedures, particularly when critical structures are involved. The patient's condition has been successfully managed with a combination of surgical and sclerotherapy interventions, ultimately resulting in symptomatic relief and cosmetic improvement.